Inhibition of histone lysine methyltransferases G9a and GLP by ejection of structural Zn(II). Issue 7 (15th April 2018) - Lenstra, Danny C.; Al Temimi, Abbas H.K.; Mecinović, Jasmin
Graphical abstract: Abstract: Histone lysine methyltransferases G9a and GLP are validated targets for the development of new epigenetic drugs. Most, if not all, inhibitors of G9a and GLP target the histone substrate binding site or/and the S-adenosylmethionine cosubstrate binding site. Here, we report an alternative approach for inhibiting the methyltransferase activity of G9a and GLP. For proper folding and enzymatic activity, G9a and GLP contain structural zinc fingers, one of them being adjacent to the S-adenosylmethionine binding site. Our work demonstrates that targeting these labile zinc fingers with electrophilic small molecules results in ejection of structural zinc ions, and consequently inhibition of the methyltransferase activity. Very effective Zn(II) ejection and inhibition of G9a and GLP was observed with clinically used ebselen, disulfiram and cisplatin.